Umowy polsko-niemieckie w sprawie amnestii z lat 1919−1922 - Cybulski, Bogdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The diplomatic actions of Polish and German Reich governments of 1919–1922 aimed at the normalization of relations between the population of Poland and Germany on the disputed areas of Upper Silesia, Greater Poland Wielkopolska and Pomerania are discussed in this article. After the First World War, the Poles living in the Prussian provinces or parts thereof: province Schlesien Opole Region, province Posen Grand Duchy of Poznań and province Westpreussen Gdańsk Pomerania undertook intensive efforts to join the inhabited land to the nascent Polish state. The local German people and the Prussian administration were against these efforts.The conflicts swelled and led to bloody confrontations Uprising in Wielkopolska and three Silesian Uprisings. Under pressure of allied powers the Polish and German governments were forced to take actions leading to the deescalation of confl icts. The article discusses one of the manifestations of these activities, namely the conclusion of the amnesty agreement signed on 1 October 1919 in Berlin, and the so-called supplementary agreement of 12 February 1921. The agreements went far beyond the typical acts of amnesty because they included all persons Poles and Germans who committed acts constituting a violation of the law or were deprived of their liberty for political or nationality reasons, or in connection with their participation in the fi
Keywords: polsko-niemiecka umowa o amnestii z 1 października 1919 r.; polsko-niemiecka umowa dodatkowa z 12 lutego 1921 r. do umowy z 1 października 1919 r.; Górny Śląsk; Wielkopolska; Pomorze w latach 1918–1922; amnestia dla Rosjan i Ukraińców - uczestników wojny polsko-radzieckiej 1920 r.